Investigating Workload Measures in the Nuclear Domain. (September 2014) - Mercado, Joseph E.; Reinerman-Jones, Lauren; Barber, Daniel; Leis, Rebecca
Research into human-system interaction, specifically focusing on workload, has intensified in the nuclear domain. Past research on workload in the Nuclear Power Plant (NPP) domain has attempted to use both subjective and physiological measures of workload, yet the sensitivity of the workload measures used in past experiments is unknown. This initial experiment will guide future research in the NPP domain by identifying whether the NASA-TLX, EEG, and ECG are sensitive to detecting workload changes in common NPP Main Control Room (MCR) tasks. Results suggest the three workload measures did not reveal expected differences between task types in the NPP MCR context.